Initial multicenter experience using a novel articulating through-the-scope traction device for endoscopic submucosal dissection - Hayat, Maham; Schlachterman, Alexander; Schiavone, Grace; Mizrahi, Meir; Park, Jong Kyu; Kumbhari, Vivek; Cheesman, Antonio; Draganov, Peter V; Hasan, Muhammad Khalid; Yang, Dennis (Endoscopy International Open, 2023)
Background and study aims A single-operator, articulating, through-the-scope (TTS) traction device was recently developed to facilitate endoscopic submucosal dissection (ESD). Clinical data on the performance of this device are limited. We report an initial multicenter experience with ESD using this articulating TTS traction device.Patients and methods Retrospective analysis on all consecutive patients who underwent ESD using this traction device (T-ESD) at five centers between August 2021 and December 2022. Endpoints included: rates of en-bloc resection, R0 resection, curative resection, and adverse events.Results Thirty-six patients (median age 64.8 years; 47.2% women) underwent ESD (median lesion size 40 mm; interquartile range [IRQ]: 27.5–67.5) for lesions in the esophagus (n=2), stomach (n=8), sigmoid colon (n=6), and rectum (n=20). Submucosal fibrosis was encountered in one-third of the lesions (33.3%). Median ESD time was 104.6 minutes (IQR: 65–122). En-bloc, R0 and curative resection were achieved in 94.4%, 91.6%, and 97.2%, respectively. The single patient with non-curative resection of an invasive rectal adenocarcinoma underwent surgery. There were no cases of delayed bleeding or perforation. There was no recurrence on surveillance endoscopy (n=20) at a median of 6 months (IQR: 3.75–6).Conclusions This initial multicenter experience demonstrates high resection rates and excellent safety profile when performing ESD with this novel articulating TTS device. Dynamic real-time traction may lower the technical difficulty of ESD. Additional studies are needed to assess its cost-effectiveness and compare its usefulness with other traction devices and techniques during ESD.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (polypectomy, ESD, EMRc, ...)